2020
DOI: 10.3390/insects11120881
|View full text |Cite
|
Sign up to set email alerts
|

Manual Sampling and Video Observations: An Integrated Approach to Studying Flower-Visiting Arthropods in High-Mountain Environments

Abstract: Despite the rising interest in biotic interactions in mountain ecosystems, little is known about high-altitude flower-visiting arthropods. In particular, since the research in these environment can be limited or undermined by harsh conditions and logistical difficulties, it is mandatory to develop effective approaches that maximize possibilities to gather high-quality data. Here we compared two different methods, manual sampling and video observations, to investigate the interactions between the high-mountain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The Alps are the highest and longest mountain range that lies entirely in Europe, and they host peculiar biodiversity, comprising several endemic plants and arthropods and threatened species [24][25][26][27][28][29]. While a significant body of literature deals with plant diversity, species occurrence, and phenology in the Alps (e.g., [30][31][32][33][34][35]), not many studies have addressed the topic of flower-visiting arthropod communities and abiotic factors impacting their activity in this environment [36][37][38][39][40][41][42][43][44][45]. The paucity of information on arthropods is a global issue in studying mountain ecosystems [46,47], although arthropods are the most abundant and diverse group of organisms [48,49] and play crucial roles in terrestrial ecosystem functioning, especially through interactions with plants [50][51][52][53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…The Alps are the highest and longest mountain range that lies entirely in Europe, and they host peculiar biodiversity, comprising several endemic plants and arthropods and threatened species [24][25][26][27][28][29]. While a significant body of literature deals with plant diversity, species occurrence, and phenology in the Alps (e.g., [30][31][32][33][34][35]), not many studies have addressed the topic of flower-visiting arthropod communities and abiotic factors impacting their activity in this environment [36][37][38][39][40][41][42][43][44][45]. The paucity of information on arthropods is a global issue in studying mountain ecosystems [46,47], although arthropods are the most abundant and diverse group of organisms [48,49] and play crucial roles in terrestrial ecosystem functioning, especially through interactions with plants [50][51][52][53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…Many Dipteran species comparing these two methods (human observations and were identified during human observations, but some species, video recordings) when investigating arthropod plantincluding Melangyna sp., foraged away from humans during pollinator networks found differing but complementary the field surveys. Interestingly, native bees were infrequently results between the methods (Bonelli et al 2020). Bonelli captured on DVR, but were present in a large proportion of et al (2020) suggested several factors that may contribute to human observations.…”
Section: Pollination Vectorsmentioning
confidence: 99%
“…Scheduled filming, that is, recording continuously within a fixed schedule, is an alternative to overcome detection issues as no individual is missed during the recording (Bonelli et al., 2020). However, almost all commercial wildlife cameras have limited programmability, cannot film for long durations (usually 60 s) and have limited power (usually eight AA batteries or power grid access required) or data storage (SD card compatibility usually <128 GB).…”
Section: Introductionmentioning
confidence: 99%